Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1965
DOI: 10.1001/archpedi.1965.02090020449013
|View full text |Cite
|
Sign up to set email alerts
|

Normal and Abnormal Small Bowel Lengths

Abstract: THE LENGTH of the small intestine in infants and children has received little attention in the literature. Our interest was aroused by an error in radiographic diagnosis. A film of the abdomen of a 1-day-old infant was interpreted as atresia of the jejunum because only two gasfilled intestinal loops were seen. At operation, the atresia was almost at the ileocecal valve, but the total bowel length was only 50 cm, thereby accounting for the misinterpretation.Standards of small intestinal length in normal infants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

1971
1971
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(10 citation statements)
references
References 9 publications
1
8
1
Order By: Relevance
“…This study confirms previous observa tions; i.e., fetal small intestinal length in creases with gestation and is related to skeletal growth [7][8][9][10][11][12], The study also extends pre vious observations, i.e., new data for total and large intestinal length and more complete data for small intestinal length, so that refer ence data are provided to estimate intestinal length in the human fetus. Accurate determination of intestinal length is important in the clinical setting.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This study confirms previous observa tions; i.e., fetal small intestinal length in creases with gestation and is related to skeletal growth [7][8][9][10][11][12], The study also extends pre vious observations, i.e., new data for total and large intestinal length and more complete data for small intestinal length, so that refer ence data are provided to estimate intestinal length in the human fetus. Accurate determination of intestinal length is important in the clinical setting.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies are largely confined to small intestinal length [6][7][8][9][10][11][12][13] with few examining large intes tinal length [11,13], The study populations were also not well defined and the effects of IUGR were not examined. Little data are available for infants weighing < 1,500 g, and from those reports it is not possible to con struct complete fetal growth curves.…”
Section: Discussionmentioning
confidence: 99%
“…This unoperated on infant whose body length was 47 cm had a 94-cm small intestine, far less than the normal range encountered in this study and the normal 5:1 ratio found by Reiquam et al 8 This finding was in contrast to that of a 6-year-old patient (body length, 94 cm) with a long¬ standing colostomy for Hirsch¬ sprung's disease of the distal colon. The small-intestine length was 486 cm, slightly more than 1 SD greater than the mean for crown-heel length.…”
Section: Resultscontrasting
confidence: 77%
“…It should also be taken into account that as the infant grows, the length of the intestine also increases. There are many reports on the length of the human intestine (Hirsch et al 1955;Underhill 1955;Sotoyama 1958;Reiquam et al 1961) but the lengths differ according to the method of measurement employed. The measured length is the shortest when a Miller Abbott tube is used in vivo (Hirsch et al 1955), while the lengths measured at autopsy (Underhill 1955;Sotoyama 1958;Reiquam et al 1961) tend to be long.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of a neonate, Benson (1958) reported it was 248 cm on average and Reiquam and co-workers (1961) reported it was about 300 cm. As body length increases, the intestine length also increases ; in the case of adults, it is as long as about 6 m (Underhill 1955; Reiquam et al 1961). When measured in vivo, it is short, being about 3 m (Hirsch 1955).…”
Section: Discussionmentioning
confidence: 99%